Dari Masjid ke Media Sosial: Perubahan Strategi Rekrutmen Radikalisme di Era Generasi Z - Kumpul, Kumpul (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
Changes in the digital communication landscape have shifted radical groups’ recruitment strategies from physical spaces such as mosques to social media platforms, which have become the primary interaction space for Generation Z. The background to this phenomenon indicates that Generation Z, characterized by high connectivity, rapid information mobility, and susceptibility to emotional narratives, is a potential target for the spread of radical ideology packaged in creative and persuasive content. The purpose of this study is to analyze the shift in radical recruitment patterns from mosques to social media, focusing on the mechanisms, appeal, and impact on the religious patterns of Generation Z. The research method used is a literature study with a qualitative approach, reviewing previous research results, reports from international institutions, and analysis of social media content. The results show that social media provides freedom for radical groups to create more personal, interactive, and visually oriented narratives through short videos, memes, and online discussions. Recruitment strategies are no longer centered on direct ideological indoctrination, but rather through soft propaganda approaches such as issues of global injustice, religious identity, and religious lifestyles associated with heroism. Mosques still play a role, but more so in strengthening networks after the initial process is carried out in cyberspace. The research conclusion confirms that social media has become a strategic space in the evolution of radicalism recruitment, and Generation Z requires strong digital-religious literacy to avoid being easily trapped in misleading narratives.